Action-research using Participatory Video. A learning experience in San Lorenzo, Castellón, Spain. - Boni, Alejandra; Millán, Gynna Farith (Commons. Revista de Comunicación y Ciudadanía Digital, 2016)
The aim of this paper is to analyse a Participatory Action Research (PAR) process undertook as part of a summer school in 2014, in the neighbourhood of San Lorenzo, Castellón–Spain. The methodology of Participatory Video (PV) was used to introduce action learning amongst attending international students; to visualize the work of local practitioners and to enhance the voice of the local community. To carry out the analysis of this experience, an original framework is developed (the ePARC cube). The cube features three axes that represent the dimensions the PV process touches upon: 1. participation, 2. knowledge, and 3. public deliberation. From this three dimensional perspective, we argue that a genuine participatory process raises issues that often cross-cut. We conclude that to take full advantage of the momentum a PV process could reach in a community to affect social change; more engagement from policy makers should be sought.